Limited sampling strategies for therapeutic drug monitoring of amikacin and kanamycin in patients with multidrug-resistant tuberculosis - Dijkstra, J.A.; van Altena, R.; Akkerman, O.W.; de Lange, W.C.M.; Proost, J.H.; van der Werf, T.S.; Kosterink, J.G.W.; Alffenaar, J.W.C. (International journal of antimicrobial agents, 2015)
•Amikacin and kanamycin are both used in the treatment of multidrug-resistant tuberculosis.•One combined model was designed based on the pooled data of all 30 plasma concentration curves.•An optimal sampling strategy was developed based on this combined model.•Sampling at 1h and 4h after drug administration allows a reliable Bayesian estimation of the AUC0–24h using the developed model. Amikacin and kanamycin are considered important and effective drugs in the treatment of multidrug-resistant tuberculosis (MDR-TB). Unfortunately, the incidence of toxicity is high and is related to elevated drug exposure. In order to achieve a balance between efficacy and toxicity, a population pharmacokinetic (PPK) model may help to optimise drug exposure. Patients with MDR-TB who had received amikacin or kanamycin as part of their treatment and who had routinely received therapeutic drug monitoring were evaluated. A PPK model was developed and subsequently validated. Using this model, a limited sampling model was developed. Eleven patients receiving amikacin and nine patients receiving kanamycin were included in this study. The median observed 24-h area under the concentration–time curve (AUC0–24h) was 77.2mgh/L [interquartile range (IQR) 64.7–96.2mgh/L] for amikacin and 64.1mgh/L (IQR 55.6–92.1mgh/L) for kanamycin. The PPK model was developed and validated using n−1 cross-validation. A robust population model was developed that is suitable for predicting the AUC0–24h of amikacin and kanamycin. This model, in combination with the limited sampling strategy developed, can be used in daily routine to guide dosing but also to assess AUC0–24h in phase 3 studies.